Novela, testimonio y memoria: consideraciones para la creación de representaciones dentro y fuera de la historia (Estudios) - Larreátegui Plaza, Pablo (2015)
The current work proposes to observe how a literary text can complement the senses that a conglomerate gives to a historical event of national importance or, even, be the access to that memory, with the purpose of bringing the event and its senses to the present and articulate them to a contemporary context. Thus, both the fact and the literary text can assume new functions or meanings in a social framework. For this, the author addresses the perspectives of Maurice Halbwachs and Paul Ricoer, mainly on memory and assumes two types of texts: Las cruces sobre el agua by Joaquín Gallegos Lara (literary) and the collection of testimonies of some survivors of the massacre of November 15th, 1922 (of a historical nature).